Preliminary analyses of tryptophan, kynurenine, and the kynurenine: Tryptophan ratio in plasma, as potential biomarkers for systemic chlamydial infections in koalas. - Chien-Jung Chen; Benjamin Kimble; Astrid Van Aggelen; Shalini Fischer; Cheyne Flanagan; Amber Gillett; Jackie Reed; Jodie Wakeman; Merran Govendir (PLoS ONE)
Chlamydiosis is the major infectious disease responsible for significant morbidity and mortality in free-living koalas. Recently, it was reported that 28.5% of koalas infected with chlamydiosis were presented with no overt clinical signs. Identification and quantification of changes in plasma biomarkers' fluctuations have the potential to enhance C. pecorum detection and facilitate the monitoring of therapeutic efficacy of antibiotics to treat this disease in koalas. Therefore, concentrations of the essential amino acid tryptophan, tryptophan's metabolite kynurenine, and the kynurenine:tryptophan ratio were quantified by high-performance liquid chromatography in the plasma of clinically normal koalas (n = 35), koalas identified with chlamydial disease (n = 35) and koalas that had other non-chlamydial co-morbidities (n = 10). Results showed that there was a significant difference between the clinically normal versus diseased, and clinically normal versus 'other' (both p < 0.001) in kynurenine plasma concentrations and kynurenine:tryptophan ratio; and also between the clinically normal and diseased in tryptophan plasma concentrations (p = 0.001). Proposed reference ranges of tryptophan, kynurenine, and kynurenine:tryptophan ratio in koalas are: 4.27-10.4 μg/mL, 0.34-1.23 μg/mL, and 0.05-0.22, respectively. Proposed optimal cut-off points to differentiate between clinically normal and diseased are: ≤ 4.75 μg/mL (tryptophan), ≥ 0.88 μg/mL (kynurenine), and ≥ 0.12 (kynurenine:tryptophan); and ≤ 7.67 μg/mL (tryptophan), ≥ 1.18 μg/mL (kynurenine), and ≥ 0.16 (kynurenine:tryptophan) to differentiate between released/recovered and euthanised of the diseased/'other' koalas. Significant differences in haematological and biochemical analytes were in the plasma globulins between the clinically normal and diseased koalas (p = 0.01), and in alkaline phosphatase between the clinically normal and 'other' koalas (p = 0.03). Although these potential biomarkers, especially tryptophan, may not be specific for detecting C. pecorum from the rest of the population, kynurenine and the kynurenine:tryptophan ratio may have a role in identifying unhealthy koalas from the clinically normal ones, irrespective of the underlying cause.